Democracia da informação no jornalismo em Salvador: ética do cuidado nos programas sensacionalistas da televisão e sua influência na opinião pública - Santos, Diego Luz (2011)
It is intended that pose a critical dissertation on the subject of manipulation and lack of ethics that are dealt with social problems of people of low social class in the programs of the networks hyped Record and SBT, Bahia. Raises the Manichean way, used by those who denounce programs, often, physical violence, through symbolic violence. It presents a quick insight into the ethics of care, followed by a brief discussion on democracy and ethics of information. He ends this dissertation with critical appraisal of sensationalist journalism and ethics, a perspective of care to another.